Perseverative Behavior on Verbal Fluency Task in Patients with Huntington's Disease: a Retrospective Study on a Large Patient Sample. (8th December 2019) - De Lucia, Natascia; Peluso, Silvio; Roca, Alessandro; De Michele, Giuseppe; Trojano, Luigi; Salvatore, Elena
Abstract: Objective: Patients with Huntington's disease (HD) may show impairments of frontal cortical–subcortical circuits with difficulties on cognitive flexibility tasks. One marker of poor flexibility is "perseveration" behavior, which refers to inappropriate and involuntary production of iterative responses not adequate to the current task demands. This study explored frequency, type, and possible cognitive mechanisms of verbal perseverations in a large sample of HD patients. Method: A sample of 128 patients with HD underwent phonological and category verbal fluency tests to assess perseverative errors, within a wide neuropsychological, psychopathological, motor, and functional assessment. Results: Perseverative errors in verbal fluency task occurred in 89 (69.5%) patients. Patients showing perseverations scored significantly lower than patients without perseverations on tasks tapping executive and motor functions and on functional independence scales. Logistic regression analysis revealed a significant independent association of verbal perseverations with scores on Trail Making Test only. Conclusions: Verbal perseverations are frequent in HD patients and are likely related with impairments of attentional switching and working memory, hampering tracking of verbal responses already produced. Perseverative behavior may serve as a useful clinical marker of cognitive and functional impairment in patients with HD.